Effects of exercise training on glucocorticoid-induced muscle atrophy: Literature review - Macedo, Anderson G. [UNESP] (2023)
Glucocorticoids (GCs) administration, such as cortisol acetate (CA) and dexamethasone (DEXA), is used worldwide due to their anti-inflammatory, anti-allergic, and immunosuppressive properties. However, muscle atrophy is one of the primary deleterious induced responses from the chronic treatment with GCs since it stimulates muscle degradation inhibiting muscle protein synthesis. Animal models allow a better understanding of the molecular pathways involved in this process of gene modulation and production of hypertrophic and atrophic proteins. The treatment with GCs, such as DEXA, promotes the reduction of hypertrophic proteins such as serine/threonine tyrosine kinase (AKT), protein kinase mammalian target of rapamycin (mTOR), and ribosomal protein S6 kinase (p70S6K) and increased gene expression or production of atrophic proteins, such as myostatin, muscle atrophic F-box (atrogin-1), or muscle ring finger protein-1 (MuRF-1). In both continuous exercise (CE) and resistance exercise (RE) forms, exercise training is used to mitigate muscle atrophy induced by GCs. The CE attenuated muscle atrophy induced by CA or DEXA in the plantaris and extensor digitorum longus muscles, while RE mitigated the DEXA-induced atrophy in plantaris and flexor hallucis longus muscles. The RE response appears to have occurred by modulation of hypertrophic proteins through increased protein production or phosphorylated/total ratio of mTOR and p70S6K and decreased atrophic protein production of MuRF-1. CE needs future research to understand the molecular pathways of its protective response.